2007
DOI: 10.4025/actascibiolsci.v29i2.445
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfológica dos tricomas foliares e caulinares de duas espécies de Lamiaceae conhecidas popularmente como “falso-boldo”

Abstract: Caracterização morfológica dos tricomas foliares e caulinares de Caracterização morfológica dos tricomas foliares e caulinares de Caracterização morfológica dos tricomas foliares e caulinares de Caracterização morfológica dos tricomas foliares e caulinares de duas espécies de Lamiaceae conhecidas popularmente como "falso duas espécies de Lamiaceae conhecidas popularmente como "falso duas espécies de Lamiaceae conhecidas popularmente como "falso duas espécies de Lamiaceae conhecidas popularmente como "falso-bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Seasonal air temperature and rainfall were some of the variables considered. On the other hand, Milaneze-Gutierre et al highlighted the fact that a variation in the quantity and color of these trichomes is possible depending on climatic conditions and stored metabolites [ 34 ]. This phenomenon is known as plant plasticity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal air temperature and rainfall were some of the variables considered. On the other hand, Milaneze-Gutierre et al highlighted the fact that a variation in the quantity and color of these trichomes is possible depending on climatic conditions and stored metabolites [ 34 ]. This phenomenon is known as plant plasticity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of them have morphological similarities, and they are known popularly as boldus, national boldo (boldo nacional), great boldo (boldo grande), skunk boldo (boldo-gambá), fake boldo (falsoboldo) among others [51,42] (fig. 3).…”
Section: In Brazilmentioning
confidence: 99%
“…Milaneze-Gutierre et al in their study for evaluating the authenticity of Plectranthus barbatus and Plectranthus grandis samples, demonstrated that the leaves of both species are morphologically similar, making it difficult to differentiate by macroscopic characteristics. But the anatomical analysis, quantity of glandular and non-glandular trichomes allowed the differentiation of two species of Plectranthus both in fresh samples and dried fragments [51]. It is necessary here to point out that the phytochemical profile which allows us to identify the presence of a group of substances that may help in identifying the plant sample in a simple, fast and economical way [59].…”
Section: In Brazilmentioning
confidence: 99%
“…The number of secretory cells, number and length of the stalk cell(s), and the density, location and arrangement of these glandular trichomes in the epidermis can vary. Their structure and ultrastructure in vegetative and reproductive organs have been widely described in the literature (Werker et al 1985;Maffei et al 1989;Werker et al 1993;Ascensão et al 1995;Serrato-Valentin et al 1997;Milaneze-Gutierre et al 2007;Martins et al 2009).…”
Section: Introductionmentioning
confidence: 99%